2011
DOI: 10.1097/fbp.0b013e3283473be4
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of economic demand and conditioned-cued reinstatement of methamphetamine-seeking or food-seeking in rats

Abstract: The present study examined whether continued access to methamphetamine or food reinforcement changed economic demand for both. The relationship between demand elasticity and cue-induced reinstatement was also determined. Male Long-Evans rats lever-pressed under increasing fixed-ratio requirements for either food pellets or methamphetamine (20 μg/50 μl infusion). For two groups, demand curves were obtained before and after continued access (12 days, 2-hr sessions) to the reinforcer under a fixed-ratio 3 schedul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 40 publications
9
30
0
Order By: Relevance
“…We compared results of the within-session BE paradigm in males and females with results from a conventional (multi-day) BE paradigm in which rats were stabilized at each FR value for multiple days (31). Following training on the conventional BE paradigm, rats were stabilized on the within-session paradigm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We compared results of the within-session BE paradigm in males and females with results from a conventional (multi-day) BE paradigm in which rats were stabilized at each FR value for multiple days (31). Following training on the conventional BE paradigm, rats were stabilized on the within-session paradigm.…”
Section: Resultsmentioning
confidence: 99%
“…These analyses allow for direct comparison of the same BE variables across species or reinforcers (26, 27). Importantly, the variables measured with this translational approach (particularly α-demand elasticity, and Q 0 – free consumption) have been shown to predict addiction behaviors in both humans (2830) and animals (16, 25, 31, 32), and may be an effective approach for developing and testing potential pharmacotherapies (16). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This report extends behavioral-economic theory (7) by establishing a strong, predictive association between economic demand and addiction-like behavior. Previous reports have found that essential value (α) predicts cue-induced reinstatement of methamphetamine seeking (40), and that long-access self-administration of cocaine increases Q 0 while decreasing α (33). Our studies replicate these findings, and significantly extend them by also showing that essential value (α) predicts cocaine-primed reinstatement, drug seeking during abstinence, and compulsive (punished) drug taking.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies investigating drug reinforcers have used Hursh and Silberberg's (2008) exponential demand model to quantify reinforcer value (e.g., Bentzley et al, 2013; Galuska et al, 2011; Koffanus & Woods, 2013). This model provides a single number – α – that quantifies the essential value of a reinforcer.…”
Section: Introductionmentioning
confidence: 99%